Rearticulating governance through carbon in theLao PDR?. (October 2015) - Dressler, Wolfram H; Mahanty, Sango; Clendenning, Jessica; To, Phuc Xuan
Interventions to 'improve' the human condition through democratic and capitalist ideals increasingly draw on capital and markets to influence governance in line with Western mandates of state building. As a major recent example, Reducing Emissions from Deforestation and Forest Degradation 'plus' (REDD+) develops new market regimes to govern, finance, and trade carbon in line with donor discourses of civil liberties, market expansion, and, more broadly, state building. Emerging REDD + networks that aim to finance and trade carbon now align with the conditionality and ideals of democratic governance, transparency, and accountability through processes of institution building (for state stability). This paper examines the connection between REDD + projects and state-making ideals in policy and practice as bilaterals and NGOs fuse the conditions and governance of one with the other. In the Lao PDR we argue that the governance machinery and interventions associated with REDD + facilitate governance agendas to manage people, goods, and carbon in line with Western narratives of robust governance, free markets, and integrity. We contend that the adoption of REDD + will nudge local markets and governance in this postsocialist bureaucracy toward such principles, but in ways that partly reinforce the state's longer term political and economic objectives. We conclude that, rather than conserve carbon per se, REDD + governance reflects a tempered, less absolute 'extraterritoriality', where its transnational influence is differentiated depending on how assumptions and ideals align with state motives in the context of forest governance, democratic reform, and rural development.